SNAP25/syntaxin4/VAMP2/Munc18-1 Complexes in Spinal Dorsal Horn Contributed to Inflammatory Pain. (1st March 2020) - Duan, Xing-Lian; Guo, Zhen; He, Yong-Tao; Li, Yin-Xia; Liu, Yan-Ni; Bai, Hu-Hu; Li, Hu-Ling; Hu, Xiao-Dong; Suo, Zhan-Wei
Highlights: SNAP25, syntaxin4, VAMP2 and Munc18-1 formed complexes in the spinal dorsal horn. Peripheral inflammation promoted the formation of SNAP25/syntaxin4/VAMP2/Munc18-1 complex. SNAP25 C-terminal blocking peptide inhibits surface and synaptic accumulation of NMDA receptor. SNAP25 C-terminal blocking peptide alleviates inflammatory pain. Abstract: Soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) have been implicated in the trafficking of postsynaptic glutamate receptors, including N-methyl-d -aspartate (NMDA)-subtype glutamate receptors (NMDARs) that are critical for nociceptive plasticity and behavioral sensitization. However, the components of SNAREs complex involved in spinal nociceptive processing remain largely unknown. Here we found that SNAP25, syntaxin4, VAMP2 and Munc18-1 were localized at postsynaptic sites and formed the complex in the superficial lamina of spinal cord dorsal horn of rats. The complex formation between these SNAREs components were accelerated after intraplantar injection of complete Freund's adjuvant (CFA), pharmacological removal of GABAergic inhibition or activation of NMDAR in intact rats. The increased SNAP25/syntaxin4/VAMP2/Munc18-1 interaction facilitated the surface delivery and synaptic accumulation of NMDAR during inflammatory pain. Disruption of the molecular interaction between SNAP25 with its SNARE partners by using a blocking peptide derived from the C-terminus of SNAP25 effectively repressed the surface and synaptic accumulation of GluN2B-containing NMDARs in CFA-injected rats. This peptide also alleviated inflammatory mechanical allodynia and thermal hypersensitivity. These data suggested that SNAREs complex assembly in spinal cord dorsal horn was involved in the inflammatory pain hypersensitivity through promoting NMDAR synaptic trafficking.